As condições sócio-ocupacionais do assistente social na assistência estudantil: uma análise a partir da realidade da Universidade Tecnológica Federal do Paraná (UTFPR) - Bavaresco, Thiane Cristina (2020)
This dissertation deals with the socio-occupational conditions of the social worker in Student Assistance at the Federal Technological University of Paraná (UTFPR). It is based on the assumption that the social worker, as an employed person, suffers the influences of the societal transformations of the capitalist system and, as a result, its implications for the working class, among which the precariousness and intensification of work. The impacts and repercussions of these transformations, in constant movement, which occurred especially after the counter-reform of the State, evidenced in Brazil since the 1990s, consolidated neoliberalism and caused changes in social policies and social life, reflecting in the various socio-occupational spaces in that social workers are. Thus, the general objective of this study is to analyze the socio-occupational conditions of the social worker in Student Assistance from the reality of UTFPR. Social Work, as a specialization of collective work, is a profession situated in the context of the socio-technical division of labor and social workers carry out their professional practice in the process of production and reproduction of social relations, in order to establish strategies for the coping with the “social issue”. With the expansion of higher education in Brazil in the first decade of the 21st century, provided by the Support Program for Federal University Restructuring and Expansion Plans (REUNI) and by the decree that instituted the National Student Assistance Program (PNAES), it expanded the socio-occupational space for social workers in Student Assistance. In this scenario, this research is of a qualitative nature, characterized as documentary, bibliographic and field, the latter being carried out through the application of a questionnaire sent via electronic mail, composed of open and closed questions, with social workers who carry out their activities in the sector responsible for Student Assistance at UTFPR, considered a recent socio-occupational space and immersed in the dynamics of social relations in its metamorphoses. In this sense, the elements that contributed to the expansion of the professional market, the conditions under which this expansion has materialized and how they affect the professional practice of social workers were questioned. The reflections made allowed us to understand that the conditions for the professional practice of social workers have been impacted by the process of productive restructuring and neoliberalism, which directly affects the subjectivity of these workers, causing problems in the workers' living conditions, such as illness. It is necessary to expand the collective organization of UTFPR social workers, with the support of entities representing the profession, in order to ensure that professional laws are complied with, especially related to the ethical and technical conditions of professional practice.